A case of carbamazepine-induced vitamin B12 deficiency and neuropathy - Jayakumar, Ilathamizhan; Mathaiyan, Jayanthi (International Journal of Basic & Clinical Pharmacology, 2018)
Drug induced Neuropathy is seen commonly in patients undergoing treatment with drugs like phenytoin, dapsone, isoniazid etc. Carbamazepine is a drug used in the treatment in the treatment of focal seizure, generalized tonic - clonic seizure and trigeminal neuralgia. It is presented a case of carbamazepine induced vitamin B12 deficiency and neuropathy. A 21 year old male presented to our hospital with complaints of history of slipping of footwear while walking, numbness, impairment of balance and unsteadiness of gait in both lower limbs. Detailed history revealed the patient was on treatment with carbamazepine for tonic - clonic seizure for three months. He is non- smoker, non -alcoholic, not on treatment with other drugs and there is no family history of diabetes mellitus/ sensory neuropathy. On examination power was normal on both lower limbs, vibration sensation was decreased in both lower limbs, sensation was reduced, joint position was affected in bilateral toe and ankle reflex was absent. Vitamin B12 level was found to be 83pg/ml. The patient was discontinued from carbamazepine and started on vitamin B12 therapy and the symptoms subsides slowly. Causality assessment done by WHO- UMC probability method and Naranjo Adverse Drug Reactions Probability Scale showed “Probable” association.